Simultaneous determination of ten preservatives in ten kinds of foods by micellar electrokinetic chromatography. (15th August 2015) - Ding, Xiao-Jing; Xie, Na; Zhao, Shan; Wu, Yu-Chen; Li, Jiang; Wang, Zhi
Highlights: A MEKC method with good accuracy and simple sample pretreatment was established. Sample pretreatment played a key role for the assay of ten preservatives in food. Satisfactory results were obtained with the PAPAS® proficiency test samples. Abstract: An improved micellar electrokinetic capillary chromatography method (MEKC) for the simultaneous determination of ten preservatives in ten different kinds of food samples was reported. An uncoated fused-silica capillary with 50 μm i.d. and 70 cm total length was used. Under the optimized conditions, the linear response was observed in the range of 1.2–200 mg/L for the analytes. The limits of detection (LOD, S / N = 3) and limits of quantitation (LOQ, S / N = 10) ranging from 0.4 to 0.5 mg/L and 1.2 to 1.5 mg/L, respectively were obtained. The method was used for the determination of sorbic and benzoic acids in two FAPAS® (Food Analysis Performance Assessment Scheme) proficiency test samples (jam and chocolate cake). The results showed that the current method with simple sample pretreatment and small reagent consumption could meet the needs for routine analysis of the ten preservatives in ten types of food products.